If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x-21=6x+36
We move all terms to the left:
3x-21-(6x+36)=0
We get rid of parentheses
3x-6x-36-21=0
We add all the numbers together, and all the variables
-3x-57=0
We move all terms containing x to the left, all other terms to the right
-3x=57
x=57/-3
x=-19
| 2p=800 | | 3x^{2}+1=301 | | 10x/7=-100 | | -15n+4=-14n-11 | | 5x-3=13x-7 | | z/3+11=-5 | | -5f-4=-10-2-5f | | 3(x+2)=5x−2x+4 | | X+6=5x-15 | | 2x-8+3x-12=4x | | 7q-3=3+6q | | 3z+2(-6z+5)=-1-9z | | -48=-2m+18 | | 27h=351 | | x3=41 | | Y2r+7=16 | | 10x-25=-7x+9 | | -7+10b=-6+10b-1 | | 5(b+2)-3b=4 | | 3x+2=17x | | 90+(3x)+(7x)=180 | | 2x+1+5=2+5x+2-1 | | -5=5(x-4) | | –3(x–1)+7x=27 | | 4-0.25x=2.5x-1.5 | | 10x-25=3x+11 | | 8h=6h– | | X+3-3=-6x | | 12(6x+4)=5(2x−8) | | -7q=8-5q | | 10w-9+14=10w+5 | | x+5/9=7 |